Cortinarius anaunianus (Agaricales, Cortinariaceae): a new species of the Humolentes clade from Italy - Fellin, Alessandro; Ercole, Enrico; Ferrari, Renato Jonny; Vizzini, Alfredo (Phytotaxa, 2021)
Cortinarius anaunianus is described as a new species within the Humolentes clade of the section Calochroi s. lato from alpine silver fir forests (Abies alba) in northeastern Italy (Val di Non, province of Trento). Phylogeny based on the combined nrDNA ITS and LSU, rpb1, rpb2 and the coded gaps of the ITS region supports the independence of C. anaunianus from the closest taxa and its sister position to C. humolens from which it differs by (i) more vivid olivaceous tinges on pileus and lamellae when young, (ii) pileus surface strongly turning ocher-brown with age and exposure (iii) growing in silver fir forests rather than in association with broadleaved trees. Photos of fresh basidiomes in field and a full description of its main macro- and micromorphological features are provided and compared to those of the morphologically most similar species.